2013
DOI: 10.1371/journal.pone.0078767
|View full text |Cite
|
Sign up to set email alerts
|

Head Movements Evoked in Alert Rhesus Monkey by Vestibular Prosthesis Stimulation: Implications for Postural and Gaze Stabilization

Abstract: The vestibular system detects motion of the head in space and in turn generates reflexes that are vital for our daily activities. The eye movements produced by the vestibulo-ocular reflex (VOR) play an essential role in stabilizing the visual axis (gaze), while vestibulo-spinal reflexes ensure the maintenance of head and body posture. The neuronal pathways from the vestibular periphery to the cervical spinal cord potentially serve a dual role, since they function to stabilize the head relative to inertial spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…Animals were alert and seated in a primate chair while in complete darkness during experiments with their heads unrestrained. Mitchell et al (2013) found that that head movement amplitudes and velocities increased with increasing (prosthesis) current amplitudes. This study demonstrated that a rhesus monkey with a normal vestibular system using a vestibular prosthesis had canal-specific, electrically evoked eye movements.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Animals were alert and seated in a primate chair while in complete darkness during experiments with their heads unrestrained. Mitchell et al (2013) found that that head movement amplitudes and velocities increased with increasing (prosthesis) current amplitudes. This study demonstrated that a rhesus monkey with a normal vestibular system using a vestibular prosthesis had canal-specific, electrically evoked eye movements.…”
Section: Introductionmentioning
confidence: 98%
“…Their eye movement results were encouraging and suggested that it is possible to use either PAM or PRM modulations to encode head movement signals in future vestibular implants. Mitchell et al (2013) explored the effects of a unilateral, 3D canal prosthesis on rhesus monkeys’ head movements. Two animals were studied: One (normal) rhesus monkey was implanted with its canals intact; another animal that had received bilateral intratympanic gentamicin that yielded profoundly reduced VOR responses, consistent with severe vestibular damage.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical stimulation was identified as an effective means for activating the vestibular system in animals already in the 1960s [19,20]. Most recent animal research efforts have concentrated on meticulously investigating the effects of electrical stimulation parameters on vestibular responses [21], focusing mainly on vestibulo-ocular responses [22,23,24,25,26,27,28,29,30,31,32,33,34], but also on orientation percepts and postural responses [35,36,37]. In humans, extralabyrinthine and intralabyrinthine surgical routes to the lateral (LAN), posterior (PAN) and superior (SAN) ampullary branches of the vestibular nerve have been described and validated in peroperative stimulation trials [38,39,40,41,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation from such a neurostimulator produces robust vestibular nystagmus in association with electrical stimulation trains of brief biphasic pulses, which is comparable to eye movements produced naturally through the VOR (Thompson et al 2012; Phillips et al, 2011; Davidovics et al 2013). In addition to VOR, electrical stimulation has been shown to drive other modalities of the vestibular system, including producing postural and head movements (Mitchell et al 2013, Phillips et al 2013) and perceptual responses (Lewis et al 2013). Therefore, initial results in animal models and human subjects have been encouraging.…”
Section: Introductionmentioning
confidence: 99%